Influence of precast foam on the pore structure and properties of fly ash-based geopolymer foams. (30th September 2020) - Gu, Gonghui; Xu, Fang; Ruan, Shaoqin; Huang, Xiaoming; Zhu, Jing; Peng, Chao
Abstract: This paper proposed a new type of fly ash-based geopolymer foams (FAGF) designed for wall insulation in buildings. The first part investigated the pore structures and properties of FAGF such as porosity, average Feret diameter (AFD), and roundness via a variation of the mix ratios and contents of precast foam. Then the results were further supported by the microstructures of pores, leading to the optimization of mix formulations of precast foam in terms of FAGF. The second part of this study explored the relationship between precast foam properties and FAGF performance. Then the influence of foam content on the pore structure parameters, fluidity, dry density, compressive strength and thermal conductivity of FAGF were measured and analyzed, revealing the mechanism of pore forming within FAGF. The results indicated that the foam in the paste was mainly controlled by five kinds of forces: surface tension Fst, internal gas pressure Pi, drainage force Fd extrusion binding force Fc and buoyancy Fb . When these forces were balanced, the foam was in a relatively stable state in the paste, resulting in the uniform pore size distribution and the excellent macro properties of FAGF.